Electronic monitoring of chemical DNA denaturation on nanocrystalline diamond electrodes with different molarities and flow rates. Issue 5 (2nd May 2013) - Murib, M. S.; van Grinsven, B.; Grieten, L.; Janssens, S. D.; Vermeeren, V.; Eersels, K.; Broeders, J.; Ameloot, M.; Michiels, L.; Ceuninck, W. De; Haenen, K.; Schöning, M. J.; et al.
Abstract Probe DNA, consisting of a 36‐mer fragment was covalently immobilized on nanocrystalline chemical vapour deposition (CVD) diamond electrodes and hybridized with a 29‐mer target DNA. In this paper, we report on the label‐free real‐time electronic monitoring of DNA denaturation upon exposure to NaOH at different flow rates and molarities, using electrochemical impedance spectroscopy as readout technology. The impedance response was separated into a denaturation time constant and a medium exchange time constant by means of a double exponential fit. It was observed that the denaturation time is dependent on the flow rate as well as on the molarity of the NaOH. Surprisingly, it was observed that at low molarities (0.05 M) the DNA does not fully denature at low flow rates. Only after flushing the flow cell a second time with 0.05 M NaOH, complete denaturation was achieved. Confocal images were obtained and plotted in 3D graphs to confirm the results. This paper provides a systematic overview of measured denaturation times for different flow rates and at different molarities of NaOH. Optimization of these parameters can be a valuable asset in the field of mutation analysis.